2011
DOI: 10.1515/sg-2011-0038
|View full text |Cite
|
Sign up to set email alerts
|

Transcript abundances of LIM transcription factor, 4CL, CAld5H and CesAs affect wood properties in Eucalyptus globulus

Abstract: Eucalyptus globulusis the main hardwood species grown in pulpwood plantations in temperate regions of the world. We have cloned six genes influencing wood quality including the LIM domain transcription factor (LIM), 4-coumarate-CoA ligase (4CL), coniferaldehyde 5-hydroxylase (CAld5H) and the three catalytic units of cellulose synthase (CesA), fromE. globulus. The transcript abundances of LIM in basal stems of ten independentE. globuluslines showed similar patterns to those of 4CL. We investigated the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…We also observed a strong positive correlation between the expression of the individual HCT genes and the KL content (Figure 4). This result concurs with our previous report that HCT plays a role in the determination of lignin content as well as 4CL [16]. The combined coefficient of determination value (R 2 ) of HCT1 and HCT2 in that study was 0.84 and this value was higher than the values determined for the association between the individual HCT gene and the percentage of KL values or 4CL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also observed a strong positive correlation between the expression of the individual HCT genes and the KL content (Figure 4). This result concurs with our previous report that HCT plays a role in the determination of lignin content as well as 4CL [16]. The combined coefficient of determination value (R 2 ) of HCT1 and HCT2 in that study was 0.84 and this value was higher than the values determined for the association between the individual HCT gene and the percentage of KL values or 4CL.…”
Section: Discussionsupporting
confidence: 92%
“…It would be interesting to see if similar results are obtained in the field. Finally, our results provide a strong dataset for selecting elite candidate trees by monitoring transcript levels of several useful genes such as 4CL [16] and HCTs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another transcription factor, the LIM domain transcription factor, binds specifically to a PAL-box element, which is thought to be an important cis -acting element of lignification-related gene expression ( Kawaoka et al, 2000 ; Kaothien et al, 2002 ). Transgenic tobacco and E. camaldulensis plants with antisense LIM show low concentrations of transcripts of some key genes such as PAL and 4CL that are involved in the lignin biosynthesis pathway ( Kawaoka et al, 2000 , 2006 ; Negishi et al, 2011 ). Thus, LIM seems to play a crucial role in lignification.…”
Section: Discussionmentioning
confidence: 99%
“…Northern and Western hybridization analyses verified that the Euc4CL1 gene expressed in secondary developing xylem tissues is associated with lignin biosynthesis (Chen et al 2006). Negishi et al (2011) found that the transcript abundances of 4CL were highly correlated with lignin content in the basal part of stems of E. globulus. In E. grandis, there is a single member Egr4CL1 in class I, which is strongly and specifically expressed in developing xylem (Carocha et al 2015).…”
Section: Introductionmentioning
confidence: 90%